Écriture phénoménologique et théologique : Fonctions du « comme », « comme si » et « en tant que » chez Jean-Luc Marion. - BASSAS VILA, Javier (Studia Phaenomenologica)
This paper intends to identify the functions of the French particle “comme” (“like” in opposition to “as”) and “comme si” (“as if”) in the work of French contemporary philosopher Jean-Luc Marion, especially in L’idole et la distance (American translation: The Idol and Distance), Dieu sans l’être (American translation: God without Being), Étant donné (American translation: Being given) and De surcroît (American translation: In excess). The author of this paper focuses on the relation between phenomenology and theology in order to demonstrate its complexity by an analysis of linguistic phenomenology. At the end of this analysis, the “saturated phenomenon”, as proposed by Jean-Luc Marion, becomes an important notion to understand the boundaries of both disciplines, phenomenology and theology